The Making of Caribbean Not-so-Natural Disasters - Gibrán Cruz- Martínez; Melissa Fernández Arrigoitia; Janialy Ortiz Camacho; Patria Román-Velazquez (Alternautas, 2022)
Hurricanes are not a novelty in the Caribbean. However, 2017 left several shocking facts for history books regarding intensity and frequency. Two Category 4 and two Category 5 hurricanes – the strongest category on the Saffir-Simpson scale – hit the Caribbean in a month's-time. Despite the label ‘natural disaster’, colonialism and human-induced factors are behind the high levels of inequality, climate change and incomplete recoveries in the Caribbean region, which increase the region's vulnerability to disaster. This special issue addresses the disaster conditions, responses and consequences not only in Puerto Rico but also in the impacted neighbouring islands of Barbuda and Cuba. We expect this to be the beginning of a number of critical social research examining the Dominica, Haïti, Turks & Caicos, Virgin Islands, Montserrat, Guadeloupe, St Kitts & Nevis, St. Martin the Dominican Republic, and the rest of Caribbean countries who encounters natural and not-so-natural disasters.